Dynamic reconfiguration of long human genes during one transcription cycle. - Larkin, J; Cook, P; Papantonis, A (2012)
We analyzed three human genes that were >200 kbp in length as they are switched on rapidly and synchronously by tumor necrosis factor alpha and obtained new insights into the transcription cycle that are difficult to obtain using continuously active, short, genes. First, a preexisting "whole-gene" loop in one gene disappears on stimulation; it is stabilized by CCCTC-binding factor and TFIIB and poises the gene for a prompt response. Second, "subgene" loops (detected using chromosome conformation capture) develop and enlarge, a result that is simply explained if elongating polymerases become immobilized in transcription factories, where they reel in their templates. Third, high-resolution localization confirms that relevant nascent transcripts (detected using RNA fluorescence in situ hybridization) lie close enough to be present on the surface of one factory. These dynamics underscore the complex transitions between the poised, initiating, and elongating transcriptional states.